Association of first-trimester HbA1c levels with adverse pregnancy outcomes in different ethnic groups. (April 2019) - Mañé, Laura; Flores-Le Roux, Juana Antonia; Gómez, Nàdia; Chillarón, Juan José; Llauradó, Gemma; Gortazar, Lucía; Payà, Antonio; Pedro-Botet, Juan; Benaiges, David
Abstract: Aim: To determine, in a multi-ethnic cohort, the association of first-trimester HbA1c levels with the development of pregnancy complications. Methods: A prospective study between April 2013–October 2016. Participants were stratified in five ethnic groups. Women had an HbA1c measurement added to their first antenatal bloods. Primary outcome was macrosomia and secondary outcomes included preeclampsia and large-for-gestational age (LGA). A multivariate logistic regression analysis was performed to adjust for potential confounders in determining the association between different HbA1c cut-off points and obstetric outcomes on each ethnic group. Results: 1, 882 pregnancies were included. Analysis was limited to the three main ethnic groups: Caucasian (54.3%), South-Central Asian (19%) and Latin-American (12.2%). There was no association between HbA1c levels and obstetric outcomes among Caucasians. In Latin-Americans, an HbA1c ≥ 5.8% (40 mmol/mol) was associated with higher risk of macrosomia, whereas an HbA1c ≥ 5.9% (41 mmol/mol) was associated with LGA. In South-Central Asian, an HbA1c ≥ 5.7% (39 mmol/mol) was associated with increased risk of macrosomia and a continuous graded relationship between HbA1c levels and preeclampsia and LGA was detected starting at HbA1c levels of 5.4% (36 mmol/mol). Conclusion: First-trimester HbA1c levels perform as a suitable predictor of pregnancy complications in South-Central Asian and Latin-American women whereas in Caucasian no significant associations were found.